Preferences and Ratings of Partner Traits in Female Survivors of Childhood Abuse With PTSD and Healthy Controls. Issue 3 (February 2021) - Lieberz, Klara A.; Müller-Engelmann, Meike; Priebe, Kathlen; Friedmann, Franziska; Görg, Nora; Herzog, Julia Isabell; Steil, Regina
There is growing empirical evidence for an association between childhood abuse (CA) and intimate partner violence (IPV) in adulthood. We tested whether revictimized survivors of severe to extreme severities of child sexual abuse (CSA) and severe severities of child physical abuse (CPA) differed from nonvictimized healthy controls in their trait preferences in intimate partners and their current mate choice. In a sample of 52 revictimized female patients with posttraumatic stress disorder (PTSD) after CSA/CPA and 52 female healthy controls, the validated Intimate Partner Preferences Questionnaire (IPPQ) was used to assess (a) the desirability of tenderness, dominance, and aggression traits in potential partners, and (b) the presence of these traits in their current intimate partners. Factors potentially associated with partner preference and mate choice, for example, chronicity of traumatic events and lower self-esteem, were explored. Our results showed that, in general, revictimized PTSD patients did not have a preference for dominant or aggressive partners. However, revictimized women displayed a significantly larger discrepancy than did healthy controls between their preferences for tenderness traits and their ratings of the presence of tenderness traits in their current partners. Our results indicated that revictimized patients had lower self-esteem values; however, these values were associated with higher demands for tenderness traits. Furthermore, our results revealed that compared with patients who experienced early-onset childhood abuse (CA), those who experienced later onset CA were more accepting of dominant traits in potential partners. Women who had experienced IPV rated their current partners to be overly dominant. A higher tolerance of dominance traits might increase the risk of IPV in a specific subgroup of abused women (women with a later onset of abuse experiences and experiences of IPV).